Reconstructing Madrasa Education through Critical Pedagogy: A Freirean Framework for Islamic Educational Reform - Alwy Ahmed Mohamed; Muhammad Ndow; Mowafg Masuwd (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study, which examines the continued dominance of transmissive and authority-centred teaching methods in madrasa education, falls under the umbrella of Islamic education reform and critical pedagogy. Many madrasas still use teaching methods that restrict students' critical involvement, dialogical interaction, and sociopolitical awareness despite continuous modernisation initiatives. By offering a revolutionary paradigm grounded in dialogical learning and critical consciousness, this article seeks to reconstruct madrasa education through the prism of Paulo Freire's critical pedagogy. This topic was chosen in response to current discussions on decolonising Islamic education and increasing its applicability in pluralistic settings. This study integrates Freirean theory with key Islamic educational ideas such as tarbiyah, shura (consultation), and moral agency through a qualitative conceptual analysis supported by a critical literature survey. According to the working hypothesis, emancipatory learning can be promoted within madrasa systems while maintaining an Islamic epistemological foundation through critical pedagogical approaches. The results show that a dialogical and participative instructional approach strengthens students' ability for reflection, ethical reasoning, and social responsibility. By providing a theoretically based reform paradigm that connects Islamic educational philosophy and Western critical pedagogy, the study advances the field. In summary, using a Freirean method to rebuild madrasa education is not only a pedagogical novelty; rather, it is a calculated move toward developing Muslim students who are socially and intellectually engaged